Karaktärisering av hästerns gångarter med accelerometerteknik - Johansson, Annelie (2011)
In today’s horse keeping, there is an increasing awareness of the importance of movement and activity for the horses comfort and tenability, while tradition has it that horses should be kept in boxes and small paddocks. In order to develop housing systems that fulfils and optimizes the horses needs regarding movement and activity, we need to know more about factors that influence the activity patterns of horses. A first step is to be able to record and analyze the gaits in horses with an automated system. This could be done by use of accelerometer data. In this pilot study, existing accelerometer technique was used to characterize the different gaits in horses (walk, trot and canter) by studying how their respective signal patterns differ and how this is influenced by the size of the horse. The accelerometers being used in this study measures the movement in three different spaces; horizontal, lateral and vertical. The collected data have been analyzed by comparing the typical amplitudes (signal strengths) for the different gaits and by studying other qualities in their signal patterns. Stride frequency, corrected values of maximum and minimum and the way that forces in different planes variate, show clear differences between walk, trot and canter and should be good starting-points to proceed the work with automatic detection of gaits in horses, using accelerometerdata.